Situação de insegurança alimentar e nutricional em famílias quilombolas maranhenses - Bruna de Moura Araujo Silva; Victor Nogueira da Cruz Silveira; Luana Lopes Padilha; Maria Tereza Borges Araújo Frota (Universidade do Estado do Rio de Janeiro, 2020)
Introduction: Food and Nutritional Security is related to housing conditions, basic sanitation, quality water, access to social programs, education, employment, and access to food consumption. Objective: To evaluate the prevalence and factors associated with food and nutritional insecurity in families from quilombola communities in Maranhão. Methods: Socioeconomic, demographic and health data were collected from 373 quilombola families, in the municipalities of Penalva and Viana - MA, in 2015, using a form applied at home. Food and nutritional insecurity was assessed using the Brazilian Food Insecurity Measurement Scale. The factors associated with food insecurity were obtained through factor analysis of latent class (p<0,05). Results: The prevalence of food and nutritional security was 20,1%, while that of food and nutritional insecurity was 79,9%, of which 32,2% were classified as mild, 25,7% moderate and 22,0% serious. Families headed by women, households with more than five people, family income per capita lower than a quarter of the minimum wage and the non-coverage by the family health strategy were the variables associated with the classes of mild and moderate insecurity (p<0,05). While in severe, all variables in the model were associated (p<0,05). Conclusion: Food and nutritional insecurity is high in the quilombola communities studied, especially the severe one. These results point to the need for public policies aimed at ensuring access to education, increasing the supply of work, guaranteeing minimum income and expanding coverage of the family health strategy in quilombola communities.